Activity-based viewpoints on early mathematical skills education - Hokkanen, Teemu (LUMAT-B: International Journal on Math, Science and Technology Education, 2022)
High quality early mathematical skills instruction requires knowledge in the areas of mathematical skills and versatile pedagogical skills in their application on the part of professional teachers and instructors. The internalization on number concept plays a significant role in the early development of thinking abilities and therefore it affects the later mastery other mathematical areas. The theory of the three stages of representation by Jerome Bruner - the purpose of which is to help the child observe information in a multisensory approach - can be applied in teaching activities. In this article these early mathematical skills and Bruner’s learning theory are presented and tied to practical teaching examples.